2015
DOI: 10.1155/2015/716462
|View full text |Cite
|
Sign up to set email alerts
|

Combined Periodontal, Orthodontic, and Prosthetic Treatment in an Adult Patient

Abstract: A 41-year-old man had a significant loss of bone and supporting tissues with pathologic migration of several teeth and several missing teeth. He was treated with an interdisciplinary therapeutic protocol that included nonsurgical periodontal therapy based on strict control of supragingival plaque, subgingival periodontal therapy, orthodontic and endodontic treatment, and replacement of restorations. The orthodontic therapy was performed in a severely reduced bone support and the presence of pathological tooth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…There was no significant difference between the groups, and the authors concluded that orthodontic treatment does not negatively influence the outcome of periodontal treatment and may even be beneficial in the long term. 27,28…”
Section: General Health Conditions and Periodontal Susceptibilitymentioning
confidence: 99%
“…There was no significant difference between the groups, and the authors concluded that orthodontic treatment does not negatively influence the outcome of periodontal treatment and may even be beneficial in the long term. 27,28…”
Section: General Health Conditions and Periodontal Susceptibilitymentioning
confidence: 99%
“…Collaboration among dental and medical specialists needs to be encouraged and well organized in order to achieve the best treatment results [3,5]. This is particularly important in adult patients [6].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Missing teeth, periodontal disease, and traumatized teeth are not uncommon among these patients. 6 Traumatic injuries to permanent incisors and their supporting structures constitute a true dental emergency and require immediate assessment and management. 7 Among traumatic dental injuries, avulsion is one of the most severe, and its prognosis is closely related to the actions taken from immediately after avulsion to tooth reimplantation.…”
Section: Introductionmentioning
confidence: 99%